2022
DOI: 10.1002/acn3.51563
|View full text |Cite
|
Sign up to set email alerts
|

Sciatic nerve microvascular permeability in type 2 diabetes decreased in patients with neuropathy

Abstract: Objectives: Clinical and histological studies have found evidence that nerve ischemia is a major contributor to diabetic neuropathy (DN) in type 2 diabetes (T2D). The aim of this study was to investigate peripheral nerve microvascular permeability using dynamic contrast enhanced (DCE) magnetic resonance neurography (MRN) to analyze potential correlations with clinical, electrophysiological, and demographic data. Methods: Sixty-five patients (35/30 with/without DN) and 10 controls matched for age and body mass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…1 . Arterial input function (AIF) was determined through a semimanual process as described in detail elsewhere [ 29 ]. Subsequently, the constant of volume transfer between plasma and the extravascular extracellular compartment (K trans ), the volume fraction of extravascular extracellular space per unit volume of tissue (V e ) and the blood plasma volume per unit volume of tissue (V p ), which represent the main radiological outcome parameters, were calculated in accordance with the extended Tofts model with 𝐶𝑀(𝑡) representing the model tissue contrast agent concentration at time t [ 30 ]:
Fig.
…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…1 . Arterial input function (AIF) was determined through a semimanual process as described in detail elsewhere [ 29 ]. Subsequently, the constant of volume transfer between plasma and the extravascular extracellular compartment (K trans ), the volume fraction of extravascular extracellular space per unit volume of tissue (V e ) and the blood plasma volume per unit volume of tissue (V p ), which represent the main radiological outcome parameters, were calculated in accordance with the extended Tofts model with 𝐶𝑀(𝑡) representing the model tissue contrast agent concentration at time t [ 30 ]:
Fig.
…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies demonstrated that dynamic contrast enhanced (DCE) magnet resonance imaging (MRI) allows the assessment of peripheral nerve microcirculation [ 17 ]. Recent studies established DCI MRI of the sciatic nerve as a novel imaging biomarker in patients with type 2 diabetes [ 18 20 ]. It was found that a decrease of the sciatic nerve capillary permeability was associated with a decline of electrophysiologic parameters and an increase in clinical neuropathy scores, such as the neuropathy deficit score that allows diagnosis of LFN but not SFN [ 20 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The research suggested an age-related decline in nerve permeability and a positive correlation between nerve microvascular permeability and body mass index. 54…”
Section: Imaging Biomarkers Of Peripheral Nerves Eajazi Et Al 97mentioning
confidence: 99%
“…In a separate study, Jende et al 54 used DCE to explore peripheral nerve perfusion in individuals with type 2 diabetes. The study documented connections between microvascular perfusion parameters (K trans and V e ) and nerve conduction characteristics, suggesting increased microvascular permeability enhances blood supply to nerve structures.…”
Section: Functional Markersmentioning
confidence: 99%